Hematopoietic Stem Cell Transplant for the Treatment of X-MAID - Henrickson, Sarah E.; Andre-Schmutz, Isabelle; Lagresle-Peyrou, Chantal; Deardorff, Matthew A.; Jyonouchi, Harumi; Neven, Benedicte; Bunin, Nancy; Heimall, Jennifer R. (Frontiers in Pediatrics, 2019)
We report outcomes after hematopoietic stem cell transplant for 3 patients with X-MAID, including 1 patient from the originally described cohort and two brothers with positive TREC newborn screening for SCID who were found to have a T-B-NK+ SCID phenotype attributable to X-linked moesin associated immunodeficiency (X-MAID). A p.Arg171Trp variant in moesin was identified via exome sequencing in the older of these siblings in the setting of low lymphocyte counts and poor proliferative responses consistent with SCID. He received reduced intensity conditioning due to CMV, and was transplanted with a T-depleted haploidentical (maternal) donor. His post-transplant course was complicated by hemolytic anemia, neutropenia and sepsis. He had poor engraftment, requiring a 2nd transplant. His younger brother presented with the same clinical phenotype and was treated with umbilical cord blood transplant following myeloablative conditioning, has engrafted and is doing well. The third case also presented with severe lymphopenia in infancy, received a matched related bone marrow transplant following myeloablative conditioning, has engrafted and is doing well. These cases represent a novel manifestation of non-radiosensitive X-linked form of T-B-NK+ SCID that is able to be detected by TREC based newborn screening and effectively treated with HCT.